2018
DOI: 10.1111/nep.13063
|View full text |Cite
|
Sign up to set email alerts
|

Membrane transport status does not predict peritonitis risk in patients on peritoneal dialysis

Abstract: Smoking and hypoalbuminaemia, but not MTS, were associated with shorter time to first peritonitis and composite endpoint of peritonitis, death and technique failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Only a few studies have analyzed the association between PET and subsequent peritonitis. Sarah So et al [ 28 ] analyzed 397 PD patients and concluded that baseline PET could not predict the 10-year peritonitis rate. The D/P ratio did increase in some, but not all patients, after long-term PD treatment; therefore, the rate of peritoneal dysfunction varies widely among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have analyzed the association between PET and subsequent peritonitis. Sarah So et al [ 28 ] analyzed 397 PD patients and concluded that baseline PET could not predict the 10-year peritonitis rate. The D/P ratio did increase in some, but not all patients, after long-term PD treatment; therefore, the rate of peritoneal dysfunction varies widely among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Higher peritoneal transport is often associated with less ultrafiltration and high albumin loss. Studies have shown that the peritoneal transport status is closely related to the mortality of PD patients [ 14 , 15 ], but few studies have explored the relationship between the peritoneal transport status and the occurrence of peritonitis episodes [ 16 ]. Limited studies have concluded that the type of peritoneal transport does not predict the occurrence of peritonitis, while others have debated over the accuracy of this conclusion [ 17 ].…”
Section: Introductionmentioning
confidence: 99%